2015
DOI: 10.3747/pdi.2014.00348
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis-Related Infection in the Older Population

Abstract: With appropriate training and adequate support, it is possible to keep the peritonitis rate of elderly peritoneal dialysis (PD) patients at a highly respectable level. In general, the latest recommendations for the treatment and prevention of PD-related infections by the International Society for Peritoneal Dialysis (ISPD) are applicable to older patients. However, there are minor differences in the spectrum of causative organisms amongst elderly patients, with coagulase-negative staphylococcal species (CNSS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 38 publications
1
17
2
1
Order By: Relevance
“…The effect of educational attainment on peritonitis risk has been discussed in several studies; lower educational level and lower socioeconomic status [3,6,17,14] are associated with higher peritonitis rates. One of our findings was at odds with previous studies in which advanced age is associated with peritonitis [30,31]. As a home-based dialysis modality, PD provides more self-managed time and space.…”
Section: Discussioncontrasting
confidence: 56%
“…The effect of educational attainment on peritonitis risk has been discussed in several studies; lower educational level and lower socioeconomic status [3,6,17,14] are associated with higher peritonitis rates. One of our findings was at odds with previous studies in which advanced age is associated with peritonitis [30,31]. As a home-based dialysis modality, PD provides more self-managed time and space.…”
Section: Discussioncontrasting
confidence: 56%
“…Higher burden of comorbidities, loss of residual kidney function, longer PD duration were identified factors associated with FP in previous studies [5,22]. The association between aging and peritonitis remains controversial [27,28], a 10-year cohort study from Taiwan revealed that aged over 65 was the only independent risk factor associated with the incidence of peritonitis [29]. On the other hand, factors such as diabetes, malnutrition, comorbidities, hypoproteinemia and anemia are well-established risk factors associated with mortality.…”
Section: Discussionmentioning
confidence: 97%
“…In the non-dialysis elderly general population, depression and frailty are additive risk factors for mortality and other adverse health outcomes [18][19][20]. In previous studies on dialysis patients, physical frailty [6,7] and depression [12,13] have each been shown to be associated with adverse clinical outcomes. Our results show that their effects in PD patients are also additive.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive impairment is present in over 20% of dialysis patients [9,10], and is associated with increased risks of mortality and adverse clinical outcome [9,11]. Similarly, depressive symptoms are present in over 50% of PD patients [10] and is associated with excessive morality and represents a risk factor of peritonitis [12,13].…”
Section: Introductionmentioning
confidence: 99%